P05.33 Extra-articular tenosynovial giant cell tumor of diffuse type in the temporal area with brain parenchymal invasion. (19th September 2018) - Park, Y; Woo, M, C; Moon, H; Moon, B; You, S
Abstract: Background: Tenosynovial giant cell tumor of diffuse type is a locally aggressive neoplasm that most commonly arises in the lower extremities. However, pure extra-articular TGCT of diffuse type invading the brain parenchyma of the temporal area without involvement of the joint has not been reported to date. Herein, we report for the first time a case of an extra-articular tenosynovial giant cell tumor of diffuse type in the temporal region with brain parenchymal invasion. Material and Methods: Imaging studies revealed an intracranial expansile mass in the temporal bone without involvement of the temporomandibular joint. The unusual location of the tumor without involvement of the joint and the presence of brain parenchymal invasion made this case challenging to diagnose. The patient underwent temporal craniotomy, and the mass was completely removed. Results: The patient underwent temporal craniotomy, and the mass was completely removed. The tumor had invaded the cerebral parenchyma of the temporal lobe; it showed adhesion to the adjacent dura and no association with the adjacent joint. The cut section of the mass was solid and yellow to brown with necrosis and hemorrhage. Microscopically, the tumor showed densely cellular sheets of mononuclear cells, irregularly distributed osteoclast-like giant cells, and hemosiderin pigments. Specifically, the mononuclear cell population was composed of small polygonal or spindle cells with pale eosinophilic cytoplasm and large mononuclear cells with ovoid or kidney-shaped nuclei displaying prominent nucleoli and vesicular chromatin, which exhibited little pleomorphism. The tumor cells were positive for CD68 on immunohistochemical staining. Conclusion: Most extra-articular tumors present as a periarticular mass with frequent involvement of the adjacent joint and cystic lesions in the adjacent bone, although on rare occasions, these lesions can be purely extra-articular.Wide excision is the treatment of choice; however, complete excision of the lesion is often impaired by the need to save an adjacent joint. Therefore, radiotherapy is recommended.